Investigating Motivational Factors on The Use of Technology in EFL Classroom - Fasa, Raden Hasby Isnaindy (English Language Education, Universitas Internasional Batam, 2023)
In recent years, many studies indicate that the use of technology plays an important role in the process EFL (English as Foreign Language) learning. It is also proven that the motivation factor influences learners’ learning processes. The aim of this study is to investigate if there is any relationship between the use of technology in Indonesian EFL university classes and the students’ motivation in learning English. To test this hypothesis, a questionnaire and students’ interview developed by Binnur (2011) were distributed among a group of 30 Indonesian EFL university students who were in EFL classes learning by internet, mobile phone and power point to be used on their English classes. Data gathered were analyzed both quantitatively and qualitatively. The result shows that Indonesian EFL university students have a positive attitude towards the use of technology in their English classes.